Critical Appraisal and Review of Management Strategies for Severe Fibrosis During Penile Implant Surgery. (1st November 2015) - Trost, Landon; Patil, Mukul; Kramer, Andrew
Abstract: Introduction: Penile corporal fibrosis represents a challenging clinical scenario for surgeons placing penile prostheses (PP). Because of its rarity, a small number of series with limited follow-up have reported outcomes in this cohort. Aim: The aim of this study was to perform a critical appraisal of the corporal excavation technique, discuss its relevance to contemporary practice, and review alternative surgical methods and outcomes. Methods: A critical review was performed of the 2006 article by Montague and Angermeier, "Corporeal excavation: new technique for penile prosthesis implantation in men with severe corporeal fibrosis." Notable inclusions and omissions were described, with emphasis placed on methodology and outcomes. A PubMed search from 1990 to June 2015 was then performed to review and summarize the literature on managing corporal fibrosis during PP surgery. Main Outcome Measures: The main outcome measures used were the major contributions and limitations of the 2006 article describing outcomes of the corporal excavation technique. Results: Corporal excavation is a relevant surgical technique for managing severe corporal fibrosis. Compared with alternatives, excavation achieves successful placement of PP without need for grafting and with few complications. The article was limited by several notable omissions including relevant patient demographic and disease characteristics, patient selection, and minimal descriptions of complications and outcomes. Alternative techniques include use of specialized dilators, counter incisions, reconstruction with graft placement, minimal scar tissue excision, and endoscopic resection. Because of limited data, no specific algorithm for managing corporal fibrosis can be prescribed. Conclusions: Corporal fibrosis is a challenging clinical scenario and requires surgical experience and specialized techniques to manage appropriately. Corporal excavation represents one of several viable techniques, which may be chosen based on surgeon's preference and clinical factors.